Kedudukan Mazhab Syafi'i dalam Undang-undang Jenayah Islam di Malaysia - Ismail, Paizah (Jurnal Fiqh, 2007)
Despite the fact that there is no provision which stipulates the preference of any mazhab or school of fiqh in the implementation of Islamic criminal law in Malaysia, past or present, the use of the views of the Shafit'ie school is always preferred. The reason behind it could be that the school is dominantly practiced in the country by the people as well as the government. The evidence can be clearly seen in the inscriptions on the historic stone of Terengganu, the Canon law of Melaka and other laws that came later. Though there`s no mention of the Shafi'ite school in the laws, their provisions were clearly based on the views of the school. The same can be seen in the current enactments of Islamic Laws of the various states of Malaysia. Judges in the Syariah Courts do not bind themselves to any of the schools including the Shafi`ite school. However, in terms of fatwas, the views of Shafi'ite school are still dominant.